Improving estimation and benchmarking of State labor force statistics. - Brown, Sharon P. (Monthly Labor Review, 2005)
This article reports on an estimation procedure introduced into the Bureau of Labor Statistics (BLS) to ensure monthly additivity of State and national estimates of economic events in the U.S. The purpose of the approach was to reduce the high variability in monthly Current Population Survey estimates due to small sample sizes. The new bivariate models incorporate a major change in the BLS approach to benchmarking, rather than continue with a retrospectively applied annual average State benchmark that reintroduces sampling error to the historical monthly estimates, the proposed approach uses a reliable real-time monthly national benchmark for controlling current State model estimates of employment and unemployment.